The Whakaari/White Island disaster. An analysis informed by sociological theories of risk - Zanini, Silvia; Bennett, Simon A. (New Zealand Journal of Health and Safety Practice, 2024)
On December 9, 2019, the volcano on Whakaari/White Island, a popular New Zealand (NZ) tourist destination, erupted. Twenty-two people died. Drawing on sociological theories of risk, most particularly on systems-thinking, this qualitative analysis describes the origins of the disaster, formulates questions for the authorities and suggests actions to reduce the chances of a repeat. It is concluded that the safety culture of NZ’s adventure tourism (AT) industry requires attention. It is also concluded that bureaucratic devices such as the adventure tourism insurance cover provided by NZ’s Accident Compensation Corporation (ACC) may have encouraged, through a risk-compensation dynamic, greater risk-taking. It is suggested that improved oversight will deliver a safer adventure tourism industry. It is recommended that the authorities investigate to what extent insurance cover influences business practices.